Biogeosynthetic recycling of iron-ore tailings for green stabilization of expansive soils - Mudassir Mehmood; Wen Nie; Yunlong Liu; Kennedy Onyelowe; Fazal E Jalal; S.S. Peng; Muhammad Umar; Viroon Kamchoom (Case Studies in Construction Materials, 2026)
Expansive soils pose a significant challenge to civil infrastructure due to their high potential for expansion and contraction. These soils exhibit poor mechanical properties, leading to severe structural damage and high maintenance costs. To address these challenges, conventional stabilization like cement or lime, are widely used; however, their production substantially increases global carbon dioxide emissions and energy requirements. Therefore, there is an urgent need to develop sustainable alternatives that enhance soil performance while minimizing environmental impact by utilizing industrial by-products. In response to this need, this study proposes a sustainable composite reinforcement scheme that combines enzyme-induced carbonate precipitation (EICP), sisal fiber (SFs) reinforcement, and iron ore tailings (IOts) to treat expansive soil by deploying laboratory testing and response surface modeling (RSM). Utilizing the experimental and validated optimal mix (0.75 mol/L EICP + 0.53% SFs + 11.7% IOts) reduced swelling pressure ~98% while increasing the unconfined compressive strength ~262%, cohesion ~78%, the angle of internal friction ~172%, Unsoaked California Bearing Ratio (CBR unsoak) from 2.4% to ~26% and CBR soak 1.7% to ~20% after 28 days curing. In addition, SEM and EDS analyses confirmed synergistic microstructural interactions, resulting in a highly reinforced soil composite. Moreover, the RSM model showed good agreement with the experimental results, with errors controlled within ±5%, validating the robustness of the model. By reusing mining waste and utilizing renewable fibers, this approach demonstrates a low-carbon, cost-effective, and scalable stabilization strategy that enhances infrastructure resilience and promotes circular economy objectives. • Expansive soil stabilized using a bio-geosynthetic system integrating EICP, sisal fibers, and iron ore tailings. • Swelling pressure cut by ~98% with significant strength and CBR improvements. • Microstructural evidence (SEM-EDS) confirms enhanced cementation and fiber-matrix interlocking. • RSM predictions matched experiments within ±5%, validating optimization. • Waste-to-resource approach aligns with circular economy and sustainability goals.
Keywords: Microbial Applications in Construction Materials; Geotechnical Engineering and Soil Stabilization; Concrete and Cement Materials Research